Tuning the size and density of faceted Co3O4 nanoparticles in LaBaCo2O5.5+δ epitaxial thin films by strain engineering. Issue 41 (5th October 2016) - Lu, Jiangbo; Cheng, Sheng; Liu, Ming; Jia, Chunlin
Abstract : The growth of truncated octahedral-shaped Co3 O4 nanoparticles in LaBaCo2 O5.5+ δ epitaxial thin films can be tuned by strains in the films, which are induced by the substrates. Abstract : Both LaBaCo2 O5.5+ δ (LBCO) thin films and Co3 O4 nanocrystals have potential applications in clean energy storage and ethanol gas detection. Herein, we report that the composite films of LaBaCo2 O5.5+ δ (LBCO) and {111} faceted Co3 O4 nanoparticles were fabricated on (La, Sr)(Al, Ta)O3 (LSAT) and SrTiO3 (STO) substrates by magnetron sputtering deposition. The LBCO films revealed an epitaxial growth on both substrates with atomically sharp interfaces and a cubic-on-cubic orientation relationship. The Co3 O4 particles were found to form at a very early stage of the film deposition and have the orientation relationship of [100]Co3 O4 //[100]LBCO and (100)Co3 O4 //(100)LBCO with the LBCO film matrix. It was found that the size and density of the Co3 O4 particles can be tuned using different substrates, which induces different strains in the films. By means of high-resolution scanning transmission electron microscopy, the 3-dimensional morphology of the Co3 O4 particles was illustrated. The formation and growth of the Co3 O4 particles are discussed with respect to the strains of the films induced from the substrates.